Digital Well-Being among Islamic Religious Education (PAI) Teachers: An Interpretive Phenomenological Study - Erba Rozalina Yulianti; Yudhi Munadi; Tutik Khoirunisa; Mohd Farhan Md Ariffin (The Magister of Islamic Education IAIN Pontianak, 2026)
This study examines how Islamic Religious Education (PAI) teachers maintain digital well-being amidst increasingly intensive technological demands that affect mental health. Using a qualitative approach with an interpretive phenomenological design, the research involved two PAI teachers from junior and senior high schools through in-depth interviews analyzed thematically. The findings reveal that technology use increases cognitive load, digital stress, and disrupts spiritual rhythm. However, Islamic values such as trustworthiness, moderation, and time management function as protective mechanisms that strengthen mental resilience. Self-regulation strategies, including notification restriction, digital scheduling, and digital detox, were found to support balance, although their effectiveness depends largely on institutional support. The novelty of this study lies in integrating the digital well-being framework with Islamic psychoeducation to conceptualize the digital–mental–spiritual balance of PAI teachers, a perspective that remains underexplored in Islamic school contexts. The findings contribute conceptually to the development of value-based digital well-being discourse and provide practical implications for designing institutional policies that protect teachers’ mental health within Islamic education settings